Pengaruh Pengelolaan Anggaran Daerah Terhadap Kinerja Institusi Pemerintah Daerah : (Studi pada SETDA Kota Banjar) - Euis Suryamah; Nurdiana Mulyantini (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
This study was initiated because there was a problem of decreasing employee work motivation. So the purpose of this study is to find out and describe: Management of the regional government budget in 2020 at the Banjar City Secretariat. The performance of regional government institutions at the Banjar City Secretariat after experiencing budget refocusing in 2020. The effect of regional budget management on the performance of regional government institutions at the Banjar City Secretariat after experiencing budget refocusing in 2020. The method used in this study is qualitative descriptive research. Based on the results of the research and discussion, it was concluded that Regional Budget Management based on respondents was in the very good category, with the highest average score occurring in the reporting dimension with an average of 252 or 85.59% (in the very good category) while the lowest score occurred in the administration dimension with an average of 211.5 or 71.69% (in the good category). To provide an interpretation of this value. If presented as a whole, the respondents' responses to Regional Budget Management were 80.04% when compared to table 4.16. then it is in the 4th interval which means that the respondents' responses to Regional Budget Management are included in the very good category. Respondents' responses to Regional Government Institution Performance with the highest score are in the relevant dimension with an average of 243 or 82.37% or in the very good category, while the lowest average score is in the Better Process dimension of 226.5 or 73.77% with a good category. If presented as a whole, the respondents' responses to Regional Government Institution Performance are 78.75% when compared to table 4.38. then it is in the 4th interval which means that the respondents' responses to Regional Government Institution Performance are included in the good category.